IMPLEMENTASI MODEL PRESTASI UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN KOLABORASI PADA SISWA KELAS V SDN 6 TANJUNG - Muhammad Bagoes Pribadi; Noorhapizah; Akhmad Riandy Agusta; Tika Puspita Widya Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the lack of learning motivation and collaboration skills, which leads to a lack of variety in learning models and student engagement. This study aims to describe learning motivation and analyze collaboration skills through the application of the PRESTASI model. The method used is Classroom Action Research (CAR) in three meetings, with 12 fifth-grade students of SDN 6 Tanjung in the second semester of the 2024/2025 academic year as subjects. The approach used is qualitative and quantitative, with data obtained through observation, interviews, and tests. The results show that student learning motivation increased from "A small portion of students are highly motivated" to "All students are highly motivated," and collaboration skills from "A small portion are skilled" to "All students are skilled." This has an impact on improving learning outcomes in the classroom. The PRESTASI model has been proven effective in improving the quality of learning and is recommended as an alternative teaching strategy.